2022
DOI: 10.2105/ajph.2021.306649
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic-Related Workplace Violence and Its Impact on Public Health Officials, March 2020‒January 2021

Abstract: Objectives. To characterize the experience and impact of pandemic-related workplace violence in the form of harassment and threats against public health officials. Methods. We used a mixed methods approach, combining media content and a national survey of local health departments (LHDs) in the United States, to identify harassment against public health officials from March 2020 to January 2021. We compared media-portrayed experiences, survey-reported experiences, and publicly reported position departures. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 11 publications
2
67
1
Order By: Relevance
“…However, the national public health enterprise has struggled for decades to recruit and retain skilled professionals due to myriad challenges—competition from the private sector, visibility of governmental public health, and staff burnout, to name a few. At each governmental level, the public health workforce has atrophied following years of underinvestment, disinvestment, and separations [ 3 , 4 , 5 ], which the COVID-19 pandemic has exacerbated, increasing negative public sentiment toward public health and increasing the prevalence of bullying and harassment of its workers [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the national public health enterprise has struggled for decades to recruit and retain skilled professionals due to myriad challenges—competition from the private sector, visibility of governmental public health, and staff burnout, to name a few. At each governmental level, the public health workforce has atrophied following years of underinvestment, disinvestment, and separations [ 3 , 4 , 5 ], which the COVID-19 pandemic has exacerbated, increasing negative public sentiment toward public health and increasing the prevalence of bullying and harassment of its workers [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic revealed the difficulty of providing nonpartisan, evidence-based communication on divisive topics. 5 , 18 This challenge has been further exacerbated by a quickly shifting evidence base and misinformation. 19 , 20 Our findings highlight the need to restore confidence in public health officials as nonpartisan experts who can engage individuals across the political spectrum.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Surveys suggest that harassment is even more common for public health leaders, with approximately 40% of public health workers in leadership positions reporting harassment. 5 , 6 Hundreds of public health officials across state and local departments have resigned, retired, or been fired, 2 , 3 , 5 contributing to workforce shortages that predate the pandemic. 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A national survey conducted by NACCHO spanning March 2020 to January 2021 found that there was a high level of harassment directed at public health officials. Among 583 LHD survey respondents, 335 departments reported a total of 1499 incidents of harassment 8. Moreover, 222 public health officials reported leaving their positions and 36% of these departures occurred alongside reports of harassment 8.…”
Section: Issues Faced During the Covid-19 Pandemicmentioning
confidence: 99%